Diffusion Tensor Imaging Along the Perivascular Space Index in Different Stages of Parkinson’s Disease - Ma, Xinxin; Li, Shuhua; Li, Chunmei; Wang, Rui; Chen, Min; Chen, Haibo; Su, Wen (Frontiers in Aging Neuroscience, 2021)
Background: The aim of this study was to evaluate the glymphatic system activity in patients with Parkinson’s disease (PD) using the diffusion tensor image analysis along the perivascular space (DTI-ALPS) methods. Methods: In total, 71 patients with idiopathic PD and 36 age- and sex-matched normal controls (NCs) were involved. Patients with PD were divided into early (n = 35) and late (n = 36) subgroups, based on Hoehn and Yahr (HY) stages. We calculated the diffusivity along the perivascular spaces (ALPS), as well as projection fibers and association fibers separately, to acquire the ALPS index. Enlarged perivascular spaces (EPVS) and periventricular white matter hyperintensities were also rated. Differences in ALPS index between the PD group and NCs and between two PD subgroups and NCs were compared. In addition, a multivariate logistic regression analysis was conducted to investigate the association between ALPS index and clinical variables. Results: Patients with PD revealed lower ALPS index than NCs (p = 0.010). The late PD group exhibited significantly lower ALPS index than NCs (p = 0.006). However, there were no marked differences noticed in ALPS index between NCs and early PD group and between the two PD subgroups. In the early PD group, there was a significantly positive correlation between ALPS index and Mini-Mental State Examination (MMSE) score (β = 0.021, p = 0.029) and a negative correlation between ALPS index and EPVS score (β = −0.050, p = 0.034), after controlling for multiple variables. In the late PD group, ALPS index was inversely associated with age (β = −0.012, p = 0.004). Conclusion: Impairment of the glymphatic system is involved in PD. DTI-ALPS index could be a promising biomarker of glymphatic system in PD.